Fertility and hatchability of KUB chicken eggs results from artificial insemination using liquid semen with carrot juice supplementation - Bintari, Intan Galuh; Iswati, Iswati; Udrayana, Setya B. Udrayana; Bakar, Abu (Fakultas Peternakan Universitas Papua, 2024)
Fertility is the success of spermatozoa in fertilizing an egg cell, while hatchability is a number that shows an egg's high or low ability to hatch. This research aims to determine the fertility and hatchability of KUB chicken eggs that have been stored cold by adding carrot juice to the basic diluent Ringer Lactate Egg Yolk. There were 60 KUB chickens divided into two treatment groups, each comprising 30 KUB hens. The group of eggs resulting from artificial insemination used fresh semen with Ringer Lactate diluent (P0), and eggs resulting from artificial insemination used liquid semen, which had been stored for 2 days with carrot juice supplemented with RLKT diluent (P1). The parameters observed were fertility and egg hatchability. Data were analyzed using descriptive analysis. The results showed that spermatozoa fertility at P0 was 87.11% while P1 was 56.09%. While the average percentage of hatchability shows a PQ result of 75.69 while P2 is 93.91%, it can be concluded that the fertility of KUB chickens using fresh semen is better than using liquid semen, but the hatchability of KUB chicken eggs using liquid semen is better than that of fresh semen. Further research is needed on the success of using liquid semen in AI applications in KUB chickens.